Hungarian Monitoring, 24 December 1989 . [Magyar rádiófigyelő], 1989. december 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Chinese reactions to Romanian events - Security Council debates Romania International Politics: - Reports on events in Romania Külpolitika: - Kínai reagálás a román fejleményekre - A Biztonsági Tanács vitája Romániáról Belpolitika: - A romániai fejleményekkel kapcsolatos jelentések